2011
DOI: 10.3109/02770903.2011.611956
|View full text |Cite
|
Sign up to set email alerts
|

U-Shaped Association between Body Mass Index and the Prevalence of Wheeze and Asthma, but not Eczema or Rhinoconjunctivitis: The Ryukyus Child Health Study

Abstract: These findings suggested that being either underweight or overweight might increase the likelihood of asthma among Japanese schoolchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
3
25
2
Order By: Relevance
“…After review of the titles and abstracts, 536 articles did not meet our inclusion criteria, and 12 were excluded 31-42 for a lack of data for the frequency of AD/eczema or BMI classification. In total, 30 studies 26,33, were included in the review, of which 20 had valid data that could be pooled to assess for the effects of overweight, 26,43,47,50,[53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] 23 for obesity, 26,33,43,45,47,50,[52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] and 26 for overweight/obesity. 26,43,44,[46]…”
Section: Literature Searchmentioning
confidence: 99%
“…After review of the titles and abstracts, 536 articles did not meet our inclusion criteria, and 12 were excluded 31-42 for a lack of data for the frequency of AD/eczema or BMI classification. In total, 30 studies 26,33, were included in the review, of which 20 had valid data that could be pooled to assess for the effects of overweight, 26,43,47,50,[53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] 23 for obesity, 26,33,43,45,47,50,[52][53][54][55][56][57][59][60][61][62][63][64][65][66][67][68][69] and 26 for overweight/obesity. 26,43,44,[46]…”
Section: Literature Searchmentioning
confidence: 99%
“…Many cross-sectional, case-control and prospective studies have reported an association between obesity and an increased risk of asthma [1][2][3][4][5][6]. Furthermore, there are some studies showing a relationship between being underweight and asthma, suggesting a U-shaped association between BMI and asthma [12][13][14]. Some studies have found the association between obesity and asthma only in females [8][9][10], however, others have not [11].…”
Section: Introductionmentioning
confidence: 99%
“…The great majority of previous studies on the association of adiposity with asthma in children used BMI as the measure of exposure and focused specifically on the highest range of BMI values (9,30,31). Only a few studies have examined associations across the whole range of BMI values with some of them reporting a linear association of BMI with asthma (1,2,7) while others reporting a U-shape association with an increased risk of asthma in both the underweight and obese groups (15)(16)(17)(18). In our study, the upper range of both measures of adiposity exhibited a positive association with asthma, which in fact appeared stronger in the case of BF% than in the respective BMI z-score category.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature suggested that most studies (9) have focused on high BMI and shown associations with asthma, mainly in girls and women (10)(11)(12). Nevertheless, some studies have reported an increased risk of asthma amongst the underweight, whereas others have reported nonlinear, U-shape associations with BMI, at least in men and boys (4,(13)(14)(15)(16)(17)(18). Furthermore, some studies found no association between BMI and asthma in early childhood but only after the onset of puberty or during advanced adolescence (10,12).…”
Section: Introductionmentioning
confidence: 99%